2020
DOI: 10.18632/oncotarget.27705
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin ameliorates tumor-induced adipose tissue atrophy and inflammation via Ghrelin receptor-dependent and -independent pathways

Abstract: Adipose tissue (AT) atrophy is a hallmark of cancer cachexia contributing to increased morbidity/mortality. Ghrelin has been proposed as a treatment for cancer cachexia partly by preventing AT atrophy. However, the mechanisms mediating ghrelin's effects are incompletely understood, including the extent to which its only known receptor, GHSR-1a, is required for these effects. This study characterizes the pathways involved in AT atrophy in the Lewis Lung Carcinoma (LLC)-induced cachexia model and those mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 104 publications
(139 reference statements)
3
44
0
Order By: Relevance
“…GHSR-null mice exhibit reduced exercise tolerance when run on treadmills [ 183 ]. Also, pharmacological antagonism of GHSR and GHSR-deletion worsen anorexia/cachexia and accelerate death in tumor-bearing rodents [ 194 , 195 ]. Given these findings, activating the ghrelin system could be a viable pharmacological approach to promote food intake and defend against hypoglycemia, body weight loss, poor exercise endurance, and death during extreme nutritional challenges including severe caloric restriction and cachexia [ 4 , 183 ].…”
Section: Theoretical Downsides To Modulating the Ghrelin System As A Means To Treat Obesity And Diabetesmentioning
confidence: 99%
“…GHSR-null mice exhibit reduced exercise tolerance when run on treadmills [ 183 ]. Also, pharmacological antagonism of GHSR and GHSR-deletion worsen anorexia/cachexia and accelerate death in tumor-bearing rodents [ 194 , 195 ]. Given these findings, activating the ghrelin system could be a viable pharmacological approach to promote food intake and defend against hypoglycemia, body weight loss, poor exercise endurance, and death during extreme nutritional challenges including severe caloric restriction and cachexia [ 4 , 183 ].…”
Section: Theoretical Downsides To Modulating the Ghrelin System As A Means To Treat Obesity And Diabetesmentioning
confidence: 99%
“…The procedures of tumour implantation (TI) and ghrelin intervention were described previously. 7 , 15 Briefly, Lewis lung carcinoma (LLC) cells (1 × 10 6 cells American Type Culture Collection, Manassas, VA) were implanted subcutaneously into the right flank of mice in tumour‐bearing groups, while the mice in control groups were injected with equal volume and number of heat‐killed LLC cells (HK) in the same area. When the tumour was palpable (~1 cm in diameter, about 7 days after TI), the tumour‐bearing mice were treated with either acylated ghrelin (Anaspect, Fremont, CA) at a dose of 0.8 mg/kg (tumour + ghrelin, T + G) or saline solution (tumour + vehicle, T + V), s.q., twice daily, at 8 a.m. and 5 p.m., for approximately 14 days; while mice in HK groups received saline solution (15 mcl, HK + V), s.q., twice/day for 2 weeks until the endpoint (21 days after TI).…”
Section: Introductionmentioning
confidence: 99%
“…Our dose selection was based on our group's experience and that of other groups. 7 , 15 , 39 In brief, the dose selected for this study has been shown to be well‐tolerated and to induce a 5–10% weight gain and a ~10% increase in food intake. 39 These changes are clinically relevant because they are similar to those seen in recent human trials where ghrelin mimetics are being used.…”
Section: Introductionmentioning
confidence: 99%
“…Its orexigenic role is well established ( 5 , 67 , 68 ); however, ghrelin also serves a function in inflammatory processes ( 69 ). The presence of ghrelin and its receptors on human leucocytes (T lymphocytes and macrophages) was noted as early as 2004 ( 70 ), with proven anti-inflammatory effects in both animal and human studies, in acute ( 71 74 ) and chronic settings ( 75 78 ), as well as in a neoplastic context ( 79 ). Ghrelin receptors have also been identified in cardiac tissue ( 80 ), where they modulate cardiac function and healing by influencing myocardial contraction ( 81 ), perfusion ( 82 ) and post-myocardial infarction-changes ( 41 , 72 , 83 ).…”
Section: Ghrelin and Its Receptorsmentioning
confidence: 99%